2021
DOI: 10.1002/app.51262
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental assessment of UV resistance of high‐density polyethylene: Screening and optimization of hindered amine light stabilizers

Abstract: Hindered amine light stabilizers (HALS) are widely used chemical stabilizers for preventing polymer degradation. In this study, the effects of type of HALS and its content in high‐density polyethylene (HDPE) over the stabilization process are investigated employing density functional theory (DFT) and experimental approach. The electrophilicity index of four types of commercial HALS are compared by DFT to select the most effective one. Besides, the HDPE sample containing a phenolic antioxidant and different con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…[ 16 ] These functional groups are the oxidative products of Norrish II reaction, which occurs during UV degradation. [ 10 ] As shown, the peak intensity of these functional groups is higher for T100‐N. It can be concluded that the higher comonomer content in polyethylene is associated with the presence of more tertiary carbons and short chains in its chemical structure.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[ 16 ] These functional groups are the oxidative products of Norrish II reaction, which occurs during UV degradation. [ 10 ] As shown, the peak intensity of these functional groups is higher for T100‐N. It can be concluded that the higher comonomer content in polyethylene is associated with the presence of more tertiary carbons and short chains in its chemical structure.…”
Section: Resultsmentioning
confidence: 91%
“…[7,8] One of the most critical factors affecting PE pipes' mechanical properties and color is the degradation caused by ultraviolet (UV) emitted from the sun. [9,10] The amorphous regions of semi-crystalline polymers are very prone to this degradation. If this happens in PE pipes, efforts to improve the amorphous region through molecular engineering will practically fail, and the product will lose its high performance in sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…For S 2p, the peaks at 168.43 and 169.5 eV belonged to the sulfonic group of AOT. 59 1 H and 13 C NMR were also used to characterize the AOT-CDs dissolved in D 2 O. The maximum peak at 4.6 ppm was derived from residual methanol in D 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, adding additives is another effective way of making polymers resistant to UV rays, such as UV absorbers, inorganic oxides, and hindered amine light stabilizers (HALSs). Rahimpour et al compared four kinds of HALSs and found that 600 ppm of HALSs could effectively suppress chain scission caused by phenolic antioxidants by scavenging polymer free radicals . Dong et al showed that the poly­(vinyl alcohol) (PVA)/SE film had excellent photostability because the bio-UV absorber SE reacted with radical oxygen as well as reduced oxygen and generated active oxygen species .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation